2017
DOI: 10.3389/fnbeh.2017.00038
|View full text |Cite
|
Sign up to set email alerts
|

Accessible Neurobehavioral Anger-Related Markers for Vulnerability to Post-Traumatic Stress Symptoms in a Population of Male Soldiers

Abstract: Identifying vulnerable individuals prone to develop post-traumatic stress symptoms (PTSS) is of paramount importance, especially in populations at high risk for stress exposure such as combat soldiers. While several neural and psychological risk factors are known, no post-traumatic stress disorder (PTSD) biomarker has yet progressed to clinical use. Here we present novel and clinically applicable anger-related neurobehavioral risk markers for military-related PTSS in a large cohort of Israeli soldiers. The psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 71 publications
0
21
1
Order By: Relevance
“…Indeed, rumination was found as a powerful predictor of persistent stress symptomatology (Michael et al, 2007 ) and in fact also as a mediator between TSS and anger (Orth et al, 2008 ). Though previous findings provided a neural link between anger and TSS (Gilam et al, 2017 ; Lin et al, 2017 ), the results found here provide a first such link between emotional coping in the aftermath of anger and stress related symptomatology. Nevertheless, our findings necessitate additional inquiry since they were limited by the relatively small sample size which consisted of males only, and that soldiers did not experience actual traumatic events and evidenced moderate levels of TSS.…”
Section: Discussioncontrasting
confidence: 42%
“…Indeed, rumination was found as a powerful predictor of persistent stress symptomatology (Michael et al, 2007 ) and in fact also as a mediator between TSS and anger (Orth et al, 2008 ). Though previous findings provided a neural link between anger and TSS (Gilam et al, 2017 ; Lin et al, 2017 ), the results found here provide a first such link between emotional coping in the aftermath of anger and stress related symptomatology. Nevertheless, our findings necessitate additional inquiry since they were limited by the relatively small sample size which consisted of males only, and that soldiers did not experience actual traumatic events and evidenced moderate levels of TSS.…”
Section: Discussioncontrasting
confidence: 42%
“…Anger seems to be promoted by stress, and reduction of one factor leads to a reduction in the other (Jun and Lee, 2017), although job stressors were associated in general with negative emotions such as anger regardless of the level of irritability of the person (Fida et al, 2014). Moreover, evidence shows that anger is a predictor for stress and stress-related psychopathology, mostly PTSD (Lin et al, 2017) because according to cognitive models of PTSD, anger has an effect on the perception of external threats (Ehlers and Clark, 2000) thus creating a vicious circle between anger and stress. Similarly, negative affect has a strong relation with stress (Watson, 1988), aggravating its negative outcomes on health (Hamama et al, 2013; Hyun et al, 2018; Ma et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The study was carried out in accordance with the recommendations of the Declaration of Helsinki and approved by the ethics committee of the Tel Aviv Sourasky Medical Center with written informed consent from all subjects. Part of the dataset was used in previous publications (see Raz et al, 2016 ; Lin et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…All subjects underwent fMRI while passively viewing an excerpt from an Israeli documentary film “Avenge But One of My Two Eyes” (Mograbi, 2005 ), that was previously used in our lab to induce anger (Raz et al, 2016 ; Lin et al, 2017 ). The excerpt introduces a fierce political confrontation between the director and soldiers at a checkpoint in the West Bank.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation